HUBUNGAN PENGETAHUAN, SIKAP, DENGAN TINDAKAN SADARI SEBAGAI DETEKSI DINI KANKER PAYUDARA PADA MAHASISWI DI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS SUMATERA UTARA TAHUN 2015 - dilla febria; Sri Rahayu Sanusi; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT BSE is a breast self-examination aims to determine the presence or absence of breast cancer in women. This examination is done by using mirrors and performed by women aged 20 years and above. The main indications of BSE (Breast Self Examination) is to detect breast cancer by observing the breast from the front, left side and right side, if there is a bump, discoloration of the skin, nipple and discharge or pus and blood. The study aims to determine the relationship of knowledge, attitude and actions BSE (Breast Self Examination) as early detection of breast cancer on a student in the Faculty of Public Health, University of North Sumatra in 2015. This type of research is descriptive analytic survey research design with cross sectional approach. Population is the whole entire student at the Faculty of Public Health, University of North Sumatra in 2015 as many as 84 people. Chi-square test results showed significant knowledge of the action (related) on BSE (Breast Self Examination) as early detection of breast cancer (p = 0.006). Attitude with significant action (related) on BSE as early detection of breast cancer (p = 0.012). Based on the results of research and discussion is concluded that there is a relationship between knowledge, attitude and student actions on BSE (Breast Self Examination) as early detection of breast cancer. For suggestions that Sumatra University School of Public Health advised to add to the subject matter in the curriculum Kespro KIA and Public Health on BSE (Breast Self Examination) as early detection of breast cancer. For a student to read books extensions knowledge about BSE impact of the dangers of breast cancer as a killer of women so that we as health workers should be prevented by reducing the risk of breast cancer as one attempt to detect breast cancer so that in case of breast cancer then immediately get treatment. Results of the study could further as a scientific reference a student at the Faculty of Public Health, University of North Sumatra to serve as an overview of BSE (Breast Self Examination) as early detection of breast cancer.